INEMO: Distributed RF-Based Indoor Location Determination with Confidence Indicator. (2008) - Li Li, Hongbin Hongbin; Shen Shen, Xingfa Xingfa; Zhao Zhao, Jun Jun; Wang Wang, Zhi Zhi; Sun Sun, Youxian Youxian
Abstract : Using radio signal strength (RSS) in sensor networks localization is an attractive method since it is a cost-efficient method to provide range indication. In this paper, we present a two-tier distributed approach for RF-based indoor location determination. Our approach, namely, INEMO, provides positioning accuracy of room granularity and office cube granularity. A target can first give a room granularity request and the background anchor nodes cooperate to accomplish the positioning process. Anchors in the same room can give cube granularity if the target requires further accuracy. Fixed anchor nodes keep monitoring status of nearby anchors and local reference matching is used to support room separation. Furthermore, we utilize the RSS difference to infer the positioning confidence. The simulation results demonstrate the efficiency of the proposed RF-based indoor location determination.